Integrating Cybersecurity Education into University Mental Health Education: Values, Challenges, and Approaches - Wu, Jinshan (Education Insights, 2026)
The rapid proliferation of digital technologies has fundamentally transformed the higher education landscape, necessitating innovative pedagogical strategies to safeguard student well-being. Integrating cybersecurity education into university mental health education not only addresses the evolving educational environment in the digital age but also provides a crucial new educational approach to enhance students’ online adaptability, psychological resilience, and self-protection awareness against cyber threats. As students increasingly navigate complex digital ecosystems, the intersection of cyber risk and psychological vulnerability becomes more pronounced. Currently, however, this interdisciplinary integration faces significant systemic challenges. These include unclear educational positioning, inadequate institutional coordination mechanisms, insufficient faculty support and training, and outdated content formats that fail to adequately meet contemporary student needs, all of which severely hinder practical effectiveness. To overcome these barriers, this paper argues that universities must proactively advance practical efforts by clarifying overarching educational objectives and establishing robust operational frameworks. Furthermore, empowering educators through targeted professional development and innovating both curriculum content and delivery methods are essential steps. By implementing these strategies, higher education institutions can achieve an effective, synergistic alignment between cybersecurity education and mental health education in terms of goals, content, and pedagogical approaches. Ultimately, this comprehensive integration will support the holistic physical and mental development of college students while simultaneously driving the essential enhancement of their digital literacy and cyber resilience in an increasingly interconnected world.